Optimization System Irrigation Using Linear Programs in the D.I. Delta Brantas Region Sidoarjo (Case Study: Dungus Intake) - Nisa, Khoirotun; Azmi Dewi Nusantara, Danayanti (UKaRsT, 2025)
Global food security is facing challenges due to climate change and increasing water needs for agriculture. One area experiencing these problems is the Dungus intake irrigation area in Sidoarjo Regency, which faces water management due to land use changes and uncertainty of water availability. As a result, the efficiency of water distribution decreases, and agricultural productivity is disrupted, so efforts are needed to optimize the irrigation system. This study aims to optimize the irrigation system in the Dungus Intake Irrigation Area to increase the efficiency of water distribution. This effort is carried out by determining the optimal planting pattern and irrigation water allocation using the linear programming method. This method is applied by considering the mainstay discharge of the Dungus intake, crop irrigation needs, and economic benefits from various cropping pattern scenarios. The results show that the mainstay discharge ranges from 0,479–0,754 m³/sec with an allocation discharge of 2.604 m³/sec. The optimal alternative cropping pattern 3, with a land area of ​​1.890 ha, consisting of rice, corn, and shallots in three planting seasons, produces a maximum profit of Rp 242.087.200.000 per year. This study can develop an irrigation optimization model based on hydrology and economics that can improve the efficiency of water distribution. This irrigation optimization model provides a reference for irrigation managers and farmers in designing better water distribution strategies that can increase agricultural yields and economic profits through more appropriate water allocation and optimal land use.